Lizards from the end of the world: Phylogenetic relationships of the Liolaemus lineomaculatus section (Squamata: Iguania: Liolaemini) - Breitman, Maria Florencia (2011)
The Liolaemus lineomaculatus section is a geographically widely distributed group of lizards from the Patagonian region of southern South America, and includes 18 described species representing the most southerly distributed Liolaemus taxa (the genus includes 228 species and extends from Tierra del Fuego north to south-central Peru). Despite high species diversity, the phylogenetic relationships of this section are unknown. In the present work we sampled all described species in the L. lineomaculatus section as well as currently undescribed candidate species to reconstruct the first complete phylogenetic hypothesis for the clade. Our data set included four anonymous nuclear loci, three nuclear protein-coding loci, and two mitochondrial genes. We compared results obtained with three different phylogenetic methods for the concatenated data set (Maximum Parsimony, Maximum Likelihood and Bayesian Inference) with a coalescent-based species tree approach (BEST), and recovered congruent, strongly-supported topological arrangements across all methods. We identified four main clades within the L. lineomaculatus section: the lineomaculatus, magellanicus, somuncurae, and kingii+. archeforus groups, for which we estimated divergence times. We discuss the taxonomic implications of these results and how the future integration of phylogeographic, niche modeling and morphological approaches will allow testing biogeographical hypotheses in this clade.